MENINGKATKAN KEMAMPUAN MOTORIK HALUS MENGGUNAKAN MEDIA LOOSE PART DI PAUD AL-BAROKAH PADA KELOMPOK B: IMPROVING FINE MOTOR ABILITY USING MEDIA LOOSE PART IN GROUP B OF AL-BAROKAH PAUD - RETMA WIDYANING ATI RETMA; IJAH AJJAH; ENDONG NURKIYAH; SITI SOLIHA; NINA YUMINAR PRIYANTI (Program Studi PG-PAUD Universitas PGRI Adi Buana Surabaya, 2023)
Early childhood education is education that is organized to encourage the overall growth and development of children. In early childhood, several aspects of development need to be stimulated, one of which is fine motor development in children. Fine motor skills in children are physical skills that involve fine muscles such as fingers that are arranged and coordinated between the eyes and hands. The purpose of this study was to find out and obtain information about activities to improve fine motor skills in group B children at PAUD Al Barokah using loose part media. This research was conducted as part of classroom action research. The object of the study was the 15 children of Al-Barokah PAUD, consisting of 5 girls and 10 boys. The classroom action research method uses the Kemmis and Taggaret models which consist of two cycles. There are four stages in each cycle, namely: 1) planning, 2) action, 3) observation, and 4) reflection.